Recommissioning and optimization of a modular photovoltaic multilevel-inverter - Hei, Yujia; Mehlmann, Gert (IEEE Power and Energy Student Summit (PESS), 2017)
With the increasing electrical demand, the traditional fossil fuels should be limited or even replaced, because of their bad influences on climate. The solar energy is obviously one of the most important renewable energies. To improve the grid connection of photovoltaics is very important. The Institute of Electrical Energy Systems of FAU has developed a multilevel inverter for module integrated photovoltaic plants. The device has been disassembled and deactivated for the past few years. Within a laboratory practicum, the inverter is rebuilt and its components are retested and redesigned according to actual requirements. The paper summarizes the work within the practicum.<br
Keywords: Multilevel Inverter; Photovoltaic